Numerical Models in Applied Problems of Heat and Mass Transfer - Biliaieva, V. V.; Shcherbyna, S. A. (Science and Transport Progress, 2025)
Purpose. The problems of farm ventilation, prediction of CO concentration fields inside farms, prediction of artificial soil heating in greenhouses are considered. To solve a complex of such problems, it is necessary to have specialized mathematical models, oriented towards users in design organizations. Development of numerical models for solving heat and mass transfer problems for agricultural facilities (farms, greenhouses). Methodology. To solve the problem of ventilation of the working room (determination of the air flow velocity field in the room), a mathematical model of the motion of a vortex-free flow of an inviscid fluid (Laplace equation for the velocity potential) is used. Numerical integration of the modeling equation is carried out using two schemes: a locally one-dimensional scheme and a conditional approximation scheme. The G. Marchuk model is used to model the mass transfer process. Splitting schemes are used for numerical integration of the modeling equation. Two numerical models are built to analyze thermal fields in a stationary environment: a two-dimensional energy equation and a one-dimensional energy equation. Two difference schemes are used for numerical integration of the two-dimensional energy equation: a conditional approximation scheme and an explicit finite-difference scheme. An implicit splitting scheme is used to solve the one-dimensional energy equation. Findings. The software implementation of the developed numerical models has been carried out. The results of computational experiments are presented. Originality. Effective mathematical models and computer codes have been developed for solving problems of aerodynamics and mass transfer in the working space, as well as the process of heat conduction in a stationary environment. The created numerical models belong to the class of "diagnostic models", that is, computer codes that implement the developed numerical models make it possible to quickly obtain estimated data on thermal or concentration fields in the study area. Practical value. The created computer codes can be used to analyze thermal and concentration fields in agricultural premises (greenhouses, farms) to analyze the efficiency of energy systems and ensure the necessary ventilation and heating modes of the environment.